2006
DOI: 10.1021/ac0614846
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Identification of Conserved Metabolites in GC/MS Data for Metabolomics and Biomarker Discovery

Abstract: Analysis of metabolomic profiling data from gas chromatography-mass spectrometry (GC/MS) measurements usually relies upon reference libraries of metabolite mass spectra to structurally identify and track metabolites. In general, techniques to enumerate and track unidentified metabolites are nonsystematic and require manual curation. We present a method and software implementation, freely available at http://spectconnect.mit.edu, that can systematically detect components that are conserved across samples withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
168
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(172 citation statements)
references
References 36 publications
0
168
0
Order By: Relevance
“…This may be due to practical difficulties surrounding sample preparation and data analysis. Our laboratory has previously developed two computational programs to facilitate metabolomic data analysis: SpectConnect for GC-MSbased metabolic profiling (26) and Metran for stable isotopic flux analysis (29). In the present study, we applied these tools for pathway analysis in lipoapoptotic cells and successfully identified phenotype-specific changes.…”
Section: Discussionmentioning
confidence: 98%
“…This may be due to practical difficulties surrounding sample preparation and data analysis. Our laboratory has previously developed two computational programs to facilitate metabolomic data analysis: SpectConnect for GC-MSbased metabolic profiling (26) and Metran for stable isotopic flux analysis (29). In the present study, we applied these tools for pathway analysis in lipoapoptotic cells and successfully identified phenotype-specific changes.…”
Section: Discussionmentioning
confidence: 98%
“…Analyses of GC-MS samples were carried out using Spectconnect (http: //spectconnect.mit.edu/), a novel software program recently developed to reduce noise (54). Although all metabolites could not be identified, we obtained 84 unique metabolite level measurements (52 intracellular measurements and 32 extracellular measurements).…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that hundreds of metabolites are present in E. coli (Styczynski et al 2007). However, these metabolites, including benzaldehyde and diacetyl, are abundant in nature.…”
Section: Discussionmentioning
confidence: 99%